The Predictability of Grit on Counselor Educators’ Competencies and Publications - Mary K DePue; Jacqueline M Swank; Jo Lauren Weaver; Ren Liu (Teaching and Supervision in Counseling, 2023)
Counselor educators are expected to engage in research and mentor doctoral students, highlighting the importance of competency in both areas. Grit predicts positive work outcomes, and we found no studies on grit in relation to counselor educator success measures. We wanted to understand the role of grit in counselor education productivity levels and necessary competencies. We recruited counselor educators at CACREP-accredited institutions with doctoral programs. We hypothesized that grit would predict both mentoring competencies and publication rates, mediated by research competencies. We tested a model with counselor educators (N = 110) and found that the relationship between grit, as measured by the Short Grit Scale, and mentoring competency, as measured by the Mentoring Competency Assessment, and the relationship between grit and number of total career publications were both partially mediated by research competencies, as measured by the Research Competencies Scale. Thus, grit is directly and indirectly related to publications and mentoring competency. Implications for counselor educators include maintaining grit and how to use self-assessment of research and mentoring competency to increase productivity.
Keywords: grit; research competencies; mentoring competencies; publication; counselor educator